Le rôle des institutions nationales et internationales pour contrer le trafic illicite des biens culturels - René Teijgeler (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Since the civil war in 1979 Afghanistan’s heritage has been exposed to severe robbery. To mitigate the plunder several measures need to be taken. Looting is a mutual problem: market countries should prevent the sale and source countries should protect artefacts. Within Afghanistan international military forces could assist train the Afghan Heritage Police and civil society should include cultural heritage in their development plans.